Optimization of the Number and Type Composition of Houses in Housing Development Using the Simplex Method (Case Study: Pesona Arjuna Residence, Malang Regency) - Abdullah, Ali; Suryo, Eko Andi; Suharyanto, Agus (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
The rising population in Indonesia has led to an increasing demand for housing, presenting opportunities and challenges for property developers. Although luxury homes yield higher profits, most consumers favor affordable housing. This study aims to optimize the quantity and type composition of homes in Pesona Arjuna Residence, Malang Regency, using the Simplex Method to maximize profits. Developers need to balance market demand and government regulations, which require including affordable and middle-income homes alongside luxury units. The Simplex Method is applied in this study to determine the ideal composition of housing units by factoring in key constraints such as available land, production costs, and market demand. The findings reveal that houses in buildings 12 type A, 18 type B, and 23 type C yield the highest profitability. The Net Present Value (NPV) of Rp 610,940,579.76 at a 10% discount rate confirms the project’s financial success, while the Internal Rate of Return (IRR) of 13.49% indicates a solid annual return on investment. A Benefit-Cost Ratio (BCR) of 1.617 further supports the project’s financial viability, though careful consideration of market fluctuations and risks is advised. This research contributes to sustainable urban planning by offering a flexible approach to housing development, enabling developers to better adapt to market trends and optimize profits while addressing community housing needs.